Guidus n. gen. (Cestoda: Tetraphyllidea), with description of a new species and emendation of the generic diagnosis of Marsupiobothrium - Ivanov, Veronica Adriana (Journal of Parasitology)
Guidus n. gen. (Cestoda, Tetraphyllidea) is proposed for 3 cestode species from skates (Bathyraja spp.: Rajiformes, Rajidae). Members of Guidus differ from those of all other phyllobothriid genera in possessing 4 sessile and conspicuously muscular, saclike bothridia; a bothridial aperture toward anterior end of scolex, and perpendicular to scolex axis; aperture surrounded by a continuous sphincter of circular muscles, and 1 marginal accessory sucker. A new species, Guidus argentinense n. sp., is described, the diagnosis of Marsupiobothrium antarcticum is emended, and it is transferred to the new genus along with Marsupiobothrium awii. These species can be easily distinguished from G. argentinense by the presence of lappets in the bothridial margin. In addition, the diagnosis of Marsupiobothrium is emended based on the redescription of the type species, Marsupiobothrium alopias. Fil: Ivanov, Veronica Adriana. Universidad de Buenos Aires. Facultad de Cs.exactas y Naturales. Departamento de Biodiversidad y Biología Experimental. Laboratorio de Helmintologia; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina